Towards World Models in AI and Natural Language Processing Applications: Emotion, Creativity and World Knowledge - Alexandris, Christina (Proceedings of the AAAI Symposium Series, 2026)
With Emotion, as a prerequisite for Creativity, mirroring hu-man behavior and human values, the modelling of world knowledge for behavior and emotion functioning as a “road-map” of key-parameters in the language(s) and/or domain(s) concerned contributes to the creation of world models for ap-plications (i.e. Sentiment Analysis, voice user interfaces -VUIs) and training data, including Large Language Models (LLMs). World models reflecting human behavior and human values in the real world can be based on world knowledge - Collective Intelligence –integrated in analysis and processing strategies from text types such as political and journalistic texts, containing socio-cultural elements and involving essential information for understanding human behavior, emotion and, ultimately, the human mind. This complex information can be processed in respect to a “three-level” framework with distinct, identifiable features, comprising the User-Group Level, the Pragmatic Level and the Prosodic -Paralinguistic Level.